2022
DOI: 10.3389/fmars.2022.816794
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies

Abstract: Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…These findings support previous research in which breeding adults from larger colonies were found to forage further afield than those from smaller colonies (Lewis et al 2001, Ballance et al 2009, Patterson et al 2022. Given the apparent links between colony size and foraging range across seabirds (Jovani et al 2016) and the availability of census data for many breeding populations (Mitchell et al 2004, Ronconi et al 2022) adjusting expectations of foraging range in relation to colony size may provide a way to refine foraging distance-based approaches in the absence of colony-specific tracking data. Longer foraging ranges also have the potential to drive inter-population differences in demography if they result in declines in the provisioning rate of chicks, constraining chick growth (Gaston et al 1983), or lower and more variable rates of adult survival (Horswill et al 2023).…”
Section: Effect Of Colony Size and Breeding Status On Foraging Rangesupporting
confidence: 83%
See 2 more Smart Citations
“…These findings support previous research in which breeding adults from larger colonies were found to forage further afield than those from smaller colonies (Lewis et al 2001, Ballance et al 2009, Patterson et al 2022. Given the apparent links between colony size and foraging range across seabirds (Jovani et al 2016) and the availability of census data for many breeding populations (Mitchell et al 2004, Ronconi et al 2022) adjusting expectations of foraging range in relation to colony size may provide a way to refine foraging distance-based approaches in the absence of colony-specific tracking data. Longer foraging ranges also have the potential to drive inter-population differences in demography if they result in declines in the provisioning rate of chicks, constraining chick growth (Gaston et al 1983), or lower and more variable rates of adult survival (Horswill et al 2023).…”
Section: Effect Of Colony Size and Breeding Status On Foraging Rangesupporting
confidence: 83%
“…We believe accounting for this amount of variation within an applied setting is likely to be important and emphasizes the preference for collecting colony-specific data when possible. As tracking at larger scale becomes more practicable and habitat modelling procedures develop, such methods may therefore begin to supersede simpler foraging range-based assumptions (Matthiopoulos et al 2022, Ronconi et al 2022). Among-individual differences appeared to be relatively important in explaining variation in Shag foraging ranges but less so in the other species examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Storm-petrel ecology may partially explain their seeming lack of infection. They forage hundreds of kilometres offshore beyond the foraging ranges of gannets, auks, and gulls that breed in NFLD, and are unlikely to contact infected allospecific birds at sea (Ronconi et al 2022). They also nest in burrows, which generally restrict contact with conspecifics, and are nocturnal (Pollet et al 2021), so they are less likely to contact allospecific birds at the colony.…”
Section: Discussionmentioning
confidence: 99%
“…However, this still relies on some level of distributional data to inform the SDMs, as well as adequate data on environmental conditions that influence seabird at-sea distributions. Tracking data can also be used to create distribution maps and provide data to SDMs, especially over discrete areas and smaller suites of species (Augé et al 2018, Carneiro et al 2020, Fauchald et al 2021, Ronconi et al 2022). However, despite the large, and increasing, amount of tracking data available, both for the breeding and nonbreeding season (Lascelles et al 2016, Oppel et al 2018, Davies et al 2021), data are still limited for many species and locations.…”
Section: Introductionmentioning
confidence: 99%